2019
DOI: 10.1021/acs.langmuir.9b00579
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intraliposomal Metallic Nanoparticle Payload Capacity Using Microfluidic-Assisted Self-Assembly

Abstract: Hybrids composed of liposomes (L) and metallic nanoparticles (NP) hold great potential for imaging and drug delivery purposes. However, the efficient incorporation of metallic nanoparticles into liposomes using conventional methodologies has so far proved to be challenging. In this study, we report the fabrication of hybrids of liposomes and hydrophobic gold nanoparticles of size 2-4 nm (Au) using a microfluidic assisted self-assembly process. The incorporation of increasing amounts of Au nanoparticles into li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Figure 3 shows the TEM characterization of the MLPs obtained with both the two-layer and three-layer devices. The images show that the MLPs formed correctly and in agreement with previous reports of MLPs synthesized via microfluidics [34,35]. The images also show that the size of the MLPs obtained for the three-layer device is slightly larger than that obtained with the two-layer device, which agrees well with the hydrodynamic diameters measured via DLS.…”
Section: Characterization Of Magnetoliposomes Using the Microfluidic ...supporting
confidence: 90%
See 1 more Smart Citation
“…Figure 3 shows the TEM characterization of the MLPs obtained with both the two-layer and three-layer devices. The images show that the MLPs formed correctly and in agreement with previous reports of MLPs synthesized via microfluidics [34,35]. The images also show that the size of the MLPs obtained for the three-layer device is slightly larger than that obtained with the two-layer device, which agrees well with the hydrodynamic diameters measured via DLS.…”
Section: Characterization Of Magnetoliposomes Using the Microfluidic ...supporting
confidence: 90%
“…Currently, liposome preparation techniques using microfluidic systems have allowed greater control over physical properties, yielding massive and robust production of MLPs with uniform size distribution, high loading efficiencies, and reduced costs [33][34][35]. Nevertheless, there is still a challenge in the separation and sample purification methods due to the minor size differences between the MLPs and the non-encapsulated nanoparticles [32,36].…”
Section: Introductionmentioning
confidence: 99%
“…Much interest has also been drawn to the microfluidic platform synthesis of liposomes, as they represent highly efficient drug delivery systems [128]. Liposomal carriers achieve selective and sufficiently precise localization of the diseased site, also ensuring a slow and sustained release [134,135], the features required for the treatment of cancers and inflammatory conditions [136], infections, meningitis, malaria, HIV, hepatitis A, and influenza [137]. Liposomes of well-controlled sizes can encapsulate small molecules, such as amphotericin B and doxorubicin [138], being proposed to deliver vaccines, anticancer drugs, and gene therapy [134].…”
Section: Nanomaterials Synthesis Platformsmentioning
confidence: 99%
“…Despite the progress, these methods pose some challenges, including the relatively large particle size distribution, heterogeneous morphology, and, most importantly, the difficulty in separating the non-encapsulated/unbound MNPs [9]. Recent reports have demonstrated that these issues can be addressed through more precise control of assembly conditions at the microscale via microfluidic devices [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, microfluidic systems have enabled the massive production of MLs with more homogeneous physicochemical, uniform size distribution, high loading efficiencies and reduced costs [4,11,10]. Despite the significant advances in the synthesis and liposomal encapsulation technologies (LET) provided by microfluidics, proper separation methods are still a major challenge.…”
Section: Introductionmentioning
confidence: 99%